Aerobic capacity of rats recovered from fetal malnutrition with a fructose-rich diet - Cambri, Lucieli Teresa [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Ribeiro, Carla [UNESP]; Rostom de Mello, Maria Alice [UNESP] (Natl Research Council Canada-n R C Research Press, 2010)
The objective of this study was to analyze the aerobic capacity, through the maximal lactate steady-state (MLSS) protocol, of rats subjected to fetal protein malnutrition and recovered with a fructose-rich diet. Pregnant adult Wistar rats that were fed a balanced (17% protein) diet or a low-protein (6% protein) diet were used. After birth, the offspring were distributed into groups according to diet until 60 days of age: balanced (B), balanced diet during the whole experimental period; balanced-fructose (BF), balanced diet until birth and fructose-rich diet (60% fructose) until 60 days; low protein-balanced (LB), low-protein diet until birth and balanced diet until 60 days; and low protein-fructose (LF), low protein diet until birth and fructose-rich diet until 60 days. It was verified that the fructose-rich diet reduced body growth, mainly in the BF group. There was no difference among the groups in the load corresponding to the MLSS (B, 7.5 +/- 0.5%; BF, 7.4 +/- 0.6%; LB, 7.7 +/- 0.4%; and LF, 7.7 +/- 0.6% relative to body weight). However, the BF group presented higher blood lactate concentrations (4.8 +/- 0.9 mmol.L(-1)) at 25 min in the load corresponding to the MLSS (B, 3.2 +/- 0.9 mmol.L(-1); LB, 3.4 +/- 0.9 mmol.L(-1); and LF, 3.2 +/- 1.0 mmol.L(-1)). Taken together, these results indicate that the ability of young rats to perform exercise was not altered by intrauterine malnutrition or a fructose-rich diet, although the high fructose intake after the balanced diet in utero increased blood lactate during swimming exercises in rats.
Keywords: malnutrition; nutritional recovery; fructose; aerobic capacity; blood lactate; maximal lactate steady state